A SUCCESSFUL REPOSITION OF VAGINAL PROLAPSE IN CORRELATION WITH BIOCHEMICAL PROFILE IN CATTLE. - RAMSINGH, L; KUMAR D, ASHOK; BABU B, RAJA (The Indian Journal of Animal Reproduction, 2021)
The vaginal and uterine prolapse are common obstetrical problems among pregnant cattle and buffaloes duringthe last quarter of gestation. In the present case, replacement of vaginal prolapse with Buhner’s sutures and biochemicalprofile during 8th month of gestation is discussed. After application of mimosa pudica on the protruded prolapsedmass prolapse was repositioned and applied bhuner sutures. The biochemical profiles revealed that the concentrationsof total protein (5.8 g DL), calcium ( 8.2 mgDL) and phosphorus ( 3.8 mgDL) were lower than the referral values of thenormal pregnant cows. Based on these values cows were treated with calcium, phosphorous and astymin intravenouslyfor 5 days and the animal was recovered unevenly and also delivered a calf after full length of gestation.
Keywords: Biochemical profiles; vaginal prolapse; Sutures; Buhner’s; Cow